Answer:
-13
Step-by-step explanation:
−2+3(1−4)−2
=−2+(3)(−3)−2
=−2+−9−2
=−11−2
=−13
hope it helped
please mark me as brainliest.
3 + 4 = 7
84 ÷ 7 = 12 = 1 (in terms of the ratio)
12 × 3 = 36, which is the answer
Hope this helps :)
Answer:
Rounding it to two decimal places, we get distance, ![d=17.35](https://tex.z-dn.net/?f=d%3D17.35)
Step-by-step explanation:
Given:
The two points are ![(9.7, -2.8)\textrm{ and }(-3.2, 8.8)](https://tex.z-dn.net/?f=%289.7%2C%20-2.8%29%5Ctextrm%7B%20and%20%7D%28-3.2%2C%208.8%29)
The distance between the two points can be obtained using the distance formula which is given as:
![d=\sqrt{(x_{2}-x_{1})^2+(y_{2}-y_{1})^2}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28x_%7B2%7D-x_%7B1%7D%29%5E2%2B%28y_%7B2%7D-y_%7B1%7D%29%5E2%7D)
Here, for the points, ![(9.7, -2.8)\textrm{ and }(-3.2, 8.8)](https://tex.z-dn.net/?f=%289.7%2C%20-2.8%29%5Ctextrm%7B%20and%20%7D%28-3.2%2C%208.8%29)
![x_{1}=9.7,x_{2}=-3.2,y_{1}=-2.8,y_{2}=8.8](https://tex.z-dn.net/?f=x_%7B1%7D%3D9.7%2Cx_%7B2%7D%3D-3.2%2Cy_%7B1%7D%3D-2.8%2Cy_%7B2%7D%3D8.8)
Therefore, the distance between the points is:
![d=\sqrt{(-3.2-9.7)^2+(8.8-(-2.8))^2}\\d=\sqrt{(-12.9)^2+(8.8+2.8)^2}\\d=\sqrt{(12.9)^2+(11.6)^2}\\d=\sqrt{166.41+134.56}\\d=\sqrt{300.97}=17.348](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28-3.2-9.7%29%5E2%2B%288.8-%28-2.8%29%29%5E2%7D%5C%5Cd%3D%5Csqrt%7B%28-12.9%29%5E2%2B%288.8%2B2.8%29%5E2%7D%5C%5Cd%3D%5Csqrt%7B%2812.9%29%5E2%2B%2811.6%29%5E2%7D%5C%5Cd%3D%5Csqrt%7B166.41%2B134.56%7D%5C%5Cd%3D%5Csqrt%7B300.97%7D%3D17.348)
Rounding it to two decimal places, we get ![d=17.35](https://tex.z-dn.net/?f=d%3D17.35)
Don't you have to multiply the Area's ?